2021
DOI: 10.1007/s12035-021-02303-2
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis-Associated Encephalopathy: from Pathophysiology to Progress in Experimental Studies

Abstract: Sepsis is an organ dysfunction caused by an uncontrolled inflammatory response from the host to an infection. Sepsis is the main cause of morbidity and mortality in intensive care units (ICU) worldwide. One of the first organs to suffer from injuries resulting from sepsis is the brain. The central nervous system (CNS) is particularly vulnerable to damage, mediated by inflammatory and oxidative processes, which can cause the sepsis-associated encephalopathy (SAE), being reported in up to 70% of septic patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 105 publications
(163 reference statements)
1
51
0
Order By: Relevance
“…BBB damage was involved in the occurrence and development of many neuroinflammatory diseases, including SAE. Therefore, many therapeutic drugs related to neurological diseases have the effect of protecting BBB ( 29 ). Our research revealed that NU9056 could alleviate the BBB damage of LPS-induced mice.…”
Section: Discussionmentioning
confidence: 99%
“…BBB damage was involved in the occurrence and development of many neuroinflammatory diseases, including SAE. Therefore, many therapeutic drugs related to neurological diseases have the effect of protecting BBB ( 29 ). Our research revealed that NU9056 could alleviate the BBB damage of LPS-induced mice.…”
Section: Discussionmentioning
confidence: 99%
“…When Omi/HtrA2 enters the cytoplasm from mitochondria, XIAP will be degraded, thus, inhibiting the degradation of caspase-9 by XIAP [ 27 29 ], and increased expression of caspase-9 activates caspase-3, ultimately causing intracellular DNA damage. It has been proved that cell apoptosis induced by external damaging stimuli is significantly reduced after mitochondrial serine protease Omi/HtrA2 is knocked down [ 30 ]. Therefore, the effect of P2X7R activation on XIAP and caspase-3-related apoptosis needs further exploration.…”
Section: Introductionmentioning
confidence: 99%
“…The severity of SAE can range from delirium to coma. Disturbance of consciousness is an early warning sign of developing sepsis in a majority of cases (1)(2)(3)(4)(5). At present, SAE was reported by some studies to have an incidence of as high as 42% (6), with a higher case fatality rate of 28-180 days, compared with that of non-SAE.…”
Section: Introductionmentioning
confidence: 99%